Live to tell the tale : combat tactics for player characters - Ammann, Keith (The monsters know what they're doing, 2020)
An introduction to combat tactics for fifth-edition Dungeons & Dragons players, Live to Tell the Tale evens the score. It examines the fundamentals of D&D battles: combat roles, party composition, attacking combos, advantage and disadvantage, Stealth and Perception, and more...including the ever-important consideration of how to run away!